Extraction of bioactive flavonoid compounds from pecah kaca (strobilanthes crispus) using supercritical carbon dioxide - Md Salleh, Liza (2010)
Due to increasingly stringent environmental regulations, supercritical fluid extraction (SFE) has gained wide acceptance in recent years as an alternative to conventional solvent extraction for separation of organic compounds in many analytical and industrial processes. Consequently, supercritical fluid extraction (SFE) as an environmentally responsible and efficient extraction technique for solid materials was introduced and extensively studied for separation of active compounds from herbs and other plants. Supercritical carbon dioxide (SC-CO2) is one of widely used SCF. This is because of its mild critical conditions ,nontoxic, non explosive, readily available and easily removable from the products. The extraction study of bioactive flavonoid using liquid organic solvents was carried out using the standard soxhlet method. From this study it found that ethanol was the best solvent for extraction of bioactive flavonoid compounds, in terms of high extract and component yield. Analysis of the bioactive flavonoid compounds extractable from S. crispus was accomplished by High Performance Liquid Chromatography (HPLC). The first part of this study investigated the effects of pressure, temperature and dynamic extraction time as dependent variables of the SC-CO2 extraction of bioactive flavonoid compounds. A full factorial in complete randomized design (CRD) was applied to obtain the best extraction conditions and mean value (k) between levels was calculated for different extraction conditions. From the k value it can be concluded that pressure (with k value of 11.79) had a dominant effect on the extraction yield after which followed by temperature (with k value of 10.85) and dynamic time (with k value of 1.53). Based on a previous study it was found that pressure and temperature were the most important conditions in the SC-CO2 extraction, therefore for the optimization of the extraction conditions, pressure and temperature with additional co-solvent (ethanol) flow rate were selected as the extraction variables. The Box Behnken Design (BBD) based on three factors and three levels was employed to obtain the optimum condition for SC-CO2. Result showed that the optimum conditions were pressure at 200 bar,temperature at 50°C and co-solvent flow rate of 5 g/min respectively. Statistically, the yield was significantly affected by pressure and co-solvent flow-rate (p<0.05), however no significant showing was found for temperature. The mathematical model was developed in order to estimate the correlation between experimental data and theoretical prediction for different parameters of SC-CO2 namely CO2 flow rate, pressure and temperature. The best extraction was obtained at CO2 flow rate of 15 g/min, pressure of 200 bar and temperature of 50°C. Under this condition, 6.87% of initial extraction yield of flavonoid compounds obtained in the leaves was extracted. The correlation between external mass transfer coefficient and the physical properties of supercritical carbon dioxide-ethanol mixture and leaves particles in term of dimensionless number was Sh= 2.368 Re 0.271 Sc 0.33, which generates AARD of 2.67%. In general, the desorption model and Sovova model is better than adsorption equilibrium model for the estimation of extraction profile.